Reverse logistics from the perspective of the circular economy - Jerzy Janczewski (Zarządzanie Innowacyjne w Gospodarce i Biznesie)
Apart from providing many advantages to enterprises, reverse logistics also minimises their negative environmental impact, which in the fullness of time translates into advantages for the whole society. Supply chain management is a linear partnership which uses classic methods of analysis of needs and forecasting. That technique was very effective in the past, and, although it might still be used in some companies, the growing number of requirements from business environments expects more productive and flexible processes and precise planning of all movements, both the traditional and reverse ones. It is not insignificant here that the next wave of logistics is approaching, the so-called consumer logistics, following on from global logistics. The characteristic feature of economically developed and rich societies is their excessive consumption and the fact that in a very short period of time they are able to use up more resources than nature is able to reprovide. For that reason, the concept of a circular economy is becoming more and more important, as well as the closed loop economy that originates from it, supported by processes and operations of reverse logistics.